Recycling Rex Trueform: adaptive reuse of an unutilised heritage site in Salt River Cape Town by giving it a new function as a textile hybrid - Le Roux, Mikayla (University of the Free State, 2021)
The garment industry is one of the largest industries in the world. Due to rapid technological advancements, the production process of textiles has changed. These changes have resulted in the production of more affordable fabrics and an increase in consumer consumption. This, in turn, has led to mass pollution generated by the production process and mass consumption that ends up in landfills at uncontrollable rates. This happens because the industry functions on a linear process where garments are produced and rapidly replaced with new garments to satisfy the fast pace of consumer demand. The South African textile industry has faced a massive decline due to the surge of international imports, particularly from China. These imports are part of the global crisis surrounding the pollution caused by the textile industry. The decline in the textile industry is reflected in the built environment in the Salt River area where numerous abandoned garment factories can be found. The Salt River area primarily functioned as Cape Town’s industrial area in the early and mid-19th century. Amongst these abandoned sites, is one that played a large role in the garment industry during the 1960s: the Rex Trueform building. Located on the corner of Queens Park Avenue and fronting Victoria Road (commonly known as Main Road) the site has been abandoned since the company’s closure in 2005. The building has been declared a provincial heritage site due to its significant contribution to not only the textile industry but also the South African modernist movement. Above all, the building is a monumental artifact that embodies the social conditions of apartheid as imposed on the built environment. In order to understand the significance of the artifact, the study investigated the history of the site and its urban, social and economic development. This included reading the book Unstitching Rex Trueform by architect and activist Ilze Wolff, which covers the depth of the history of the Rex Trueform company and the buildings involved. Leaving industrial heritage sites abandoned risks the degeneration of the social and cultural history of communities and cities. This intervention hopes to give new life to the existing building, whilst celebrating it as a significant artefact. This new life acknowledges the value that resides within the building’s rich history and creates awareness of the textile recycling industry, while activating the forgotten site. In essence, the building will be “recycled” and, within the building, recycling will be “built”.
Dissertation (M.Arch. (Architecture))--University of the Free State, [2021]
Keywords: Clothing trade -- South Africa -- Cape Town; Rex Trueform; Textile hybrid; Textile recycling industry